Glycemic meritocracy, sport and care: Between lay expertise and medical recognition - Jean-Charles Vauthier; Bernard Kabuth (PLoS ONE, 2026)
Objective To explore the physician–patient relationship among individuals with type 1 diabetes engaged in extreme endurance sports, highlighting dynamics of recognition, autonomy, and negotiation in care. Methods Qualitative study based on thirteen semi-structured interviews with French-speaking runners living with type 1 diabetes. Analysis followed a constructivist grounded theory approach, with inductive coding and triangulation. Results The findings reveal a complex relational dynamic structured by gaps in medical expertise, the emergence of experiential autonomy, evolving forms of collaboration, and persistent structural constraints. These dynamics reflect a tension between standardized biomedical knowledge and situated, experience-based practices. Recognition of patient expertise appears conditional, often depending on the ability to maintain acceptable glycemic outcomes. Conclusion This study identifies an implicit model, termed glycemic meritocracy, in which patient autonomy and legitimacy are shaped by conformity to biomedical norms. These findings highlight the need to move beyond performance-based evaluations of care and to more fully integrate experiential knowledge into clinical practice, particularly in complex or atypical contexts.